A role of аль-Фараби is in history of science. - Baitukaeva., D. (Journal of Oriental Studies, 2016)
This article deals with a brief review of al-Farabi contribution to science. Abu Nasr al-Farabi was the greatest philosopher and scientist of his time. He completed his education at Farab and Bukhara but, later on, he went to Baghdad , where he studied and worked for a long time. During this period al-Farabi acquired mastery over several languages as well as various branches of knowledge and technology.